KEHIDUPAN DAN KARAKTERISTIK PEMIKIRAN HUKUM IMAM AHMAD BIN HANBAL - Nadia Nadia (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
Ahmad Ibn Hanbal, who is an expert in the fields of hadith and Islamic jurisprudence. He is known as the founder of the Hanbali mazhab. Many assume that Ibn Hanbal is not a fukaha but only a muhaddis, an expression like this is based on his interest in deepening the field of hadith and the many hadiths he has collected and the fatwa that tends to follow Imam Shafi'i who is his teacher, which is a strong reason for the assumption. make it interesting to review what life really is like and the characteristics of his legal thought. Ahmad Ibn Hanbal is not someone who is fanatical about his fatwas and he has a method of istimbath that is different from other Imams by giving more portions to nash than ra’yu.